Feasibility of the chosen inventory management model in a manufacturing company : A case study - Rautalin, Ulla-Maija (My University, 2023)
Globalization has led to increased business uncertainties and disruptions. For example, COVID-19 challenged most supply chains by affecting stocking and inventory flow management. As a result, the importance of inventory management has increased, as inventories act as a protection against uncertainties. On the other hand, they also tie a lot of capital. Consequently, many organizations have implemented an information system to ensure efficient inventory management. However, many companies have difficulties synchronizing their visions and strategy as part of their inventory management decisions. This research focuses on the feasibility of the chosen inventory management model in a manufacturing company. The aim of this research is to interpret the chosen inventory management model and determine to what extent it fits the case organization´s inventory management strategy and reflects the operating environment´s needs. In addition, the study aims to identify how the SCM system X´s inventory management model affects the case company´s operations. To meet this twofold research aim, a literature review of relevant literature was carried out and practical research was implemented. The latter was conducted using a qualitative case study as a method. The research data was collected with semi-structured interviews by interviewing a total of five interviewees from the case company and the SCM system X´s reseller organization. The data was analyzed with theory-guided content analysis, and finally, the results were structured using the feasibility framework created on the basis of the literature review. The framework outlined the relationship between the three strategic levels of the company´s inventory management and the SCM system´s decision support system, but also described the impact of the information technology use on organizational processes. The findings underline that the SCM system X and its inventory management model are in line with the strategic and tactical levels of the case company, as their main target is to increase availability and reduce inventories. However, from the availability point of view, the minimum service level must be separately set for the most strategically important customers so that the optimization of the inventory management model supports the case company´s strategy. At the operational level, the case company´s ERP was relatively compatible with the SCM system, whereas the optimization logic of the inventory management model raised the need for the case company to identify its strategically important products and set a minimum service level for them. In addition, based on the results, the ABC classification used by the case organization was advised to abandon. However, if the classification is needed, it was suggested to follow a multi-criteria approach instead of a single criterion in order to better identify strategically important products. The main conclusion drawn from this study is that the chosen inventory management model mainly fits the case company´s inventory management strategy but requires some changes to the case company´s processes to achieve more benefits of the SCM system X. In addition, the implementation of the system has had both direct and indirect impacts on the organization's business, most of which are positive.

Globalisaatio on johtanut liiketoiminnan epävarmuuksien ja häiriöiden lisääntymiseen. Esimerkiksi COVID-19 haastoi useimmat toimitusketjut vaikuttaen varastoinnin ja varastojen virtojen hallintaan. Tämän seurauksena varastonhallinnan merkitys on kasvanut, sillä varastot toimivat suojana epävarmuuksia vastaan. Toisaalta koska varastot sitovat myös paljon pääomaa, monet organisaatiot ovat ottaneet käyttöönsä tietojärjestelmän varmistaakseen tehokkaan varastonhallinnan. Monilla organisaatioilla on kuitenkin ollut vaikeuksia yhdistää visionsa ja strategiansa osaksi varastonhallinnan päätöksiään. Tämä tutkimus keskittyy valitun varastonhallintamallin toteutettavuuteen valmistavassa yrityksessä. Tutkimuksen tarkoituksena on tulkita valittua varastonhallintamallia ja määritellä miltä osin se sopii case-yrityksen varastonhallintastrategiaan ja heijastaa sen toimintaympäristön tarpeita. Lisäksi tutkimus pyrkii tunnistamaan, miten toimitusketjujärjestelmä X:n varastonhallintamalli vaikuttaa case-yrityksen operaatioihin. Tutkimustavoitteiden saavuttamiseksi tehtiin kirjallisuuskatsaus sekä toteutettiin tutkimuksen empiirinen osuus. Tutkimusmetodina käytettiin laadullista case-tutkimusta. Tutkimusaineisto kerättiin puolistrukturoiduilla haastatteluilla haastattelemalla yhteensä viittä haastateltavaa case-yrityksestä ja toimitusketjujärjestelmä X:n jälleenmyyjäorganisaatiosta. Aineisto analysoitiin teoriaohjaavaa sisällönanalyysiä käyttämällä, ja lopulta tulokset jäsenneltiin toteutettavuusviitekehyksen avulla, joka luotiin kirjallisuuskatsaukseen pohjalta. Viitekehyksessä hahmoteltiin organisaation varastonhallinnan kolmen strategisen tason suhdetta toimitusketjujärjestelmän päätöksenteon tukijärjestelmään sekä kuvailtiin tietotekniikan käytön vaikutuksia organisatorisiin prosesseihin. Tutkimustulokset osoittavat, että toimitusketjujärjestelmä X ja sen varastonhallintamalli ovat linjassa case-organisaation strategisen ja taktisen tason tavoitteiden kanssa, sillä molempien päätavoitteina on lisätä saatavuutta sekä vähentää varastoja. Saatavuuden näkökulmasta minimipalvelutaso tulisi kuitenkin asettaa erikseen strategisesti tärkeimmille asiakkuuksille, jotta varastonhallintamallin optimointi toimii case-yrityksen strategiaa tukien. Vastaavasti operatiivisella tasolla case-yrityksen ERP-järjestelmä nähtiin jokseenkin yhteensopivana toimitusketjujärjestelmän kanssa, kun taas varastonhallintamallin optimointilogiikan myötä esiin nousi tarve tunnistaa strategisesti tärkeät tuotteet ja minimipalvelutasojen asettaminen niille. Lisäksi tulosten pohjalta case-yrityksen ABC-luokittelusta ehdotettiin luovuttavan. Mikäli luokittelusta ei kuitenkaan haluta luopua kokonaan, ehdotettiin ottamaan käyttöön monikriteerinen menetelmä yksikriteerisen menetelmän sijaan, jotta strategisesti tärkeät tuotteet saataisiin paremmin tunnistettua. Tutkimuksen johtopäätöksinä voidaan todeta, että valittu varastonhallintamalli on linjassa pääosin case-yrityksen strategian kanssa, mutta vaatii kuitenkin joitakin muutoksia case-yrityksen prosesseihin. Lisäksi toimitusketjujärjestelmän käyttöönotolla on ollut sekä suoria että epäsuoria vaikutuksia case-yrityksen liiketoimintaprosesseihin, joista suurin osa on ollut positiivisia.
Keywords: feasibility, inventory management, inventory management model, manufacturing company, decision support system